KAJIAN KESIAPSIAGAAN PEMERINTAH KABUPATEN SLEMAN DALAM MENGANTISIPASI BENCANA ERUPSI GUNUNG MERAPI TAHUN 2010 - , ADITYA PURNOMO, S.IP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The 2010 Merapi Eruption has characteristic that show the increasing of vulcanic activities and different that its before. Therefore, it cannot easily predict the time of eruption, intensity and the spread of vulcanic materials. Sleman Regencyâs disaster preparedness is needed to make sure the efective respon when the time of eruption come. The fact is the disaster preparedness of Sleman regency is up and down, its very dynamic. Therefore, its necessary to know, monitor and determine these preparedness. The study was conducted to determine how preparedness in anticipation of Sleman Regency to the 2010 Merapi eruption and the factors that influence preparedness. To achieve the purpose of research, the author uses descriptive method with qualitative approaches. In order to get a clear picture, data collection is done through in-depth interviews, observation, and study documentation. The results showed that the Regency of Sleman less prepared to face the 2010 Merapi eruption. These conditions can be seen from parameters as follows: The Sleman Regency 2010 identified the 2010 Merapi Eruption based only on the typical characteristic of Merapi eruption, so there is less anticipation of the eruption beside the norm